Islam, Islamic Law and Constitution Making: International and Domestic Engagement in the Constitution-Making Process in Afghanistan - Rofii, Ahmad (IAIN Samarinda, 2020)
The making of the 2004 Constitution was a significant moment amidst the continuing conflicts in Afghanistan. It was an attempt to transform differences and conflicts into a shared agenda for the future of the country. The process of constitution-making in Afghanistan was marked by intense negotiations between the international community and actors, on the one hand, and domestic actors, on the other. The outcome would be called a â€œwin-win solutionâ€. This essay focuses on the making of the Islam-related clauses: How was the public participation? How has the negotiation been undertaken? What was the result and why? This essay is an attempt to answer those questions. It will argue that the process of constitution-making in Afghanistan particularly with regard to the Islam clauses is the acts of negotiations between different competing actors. The Constitution is the product of negotiations not only between international and domestic actors, but also between domestic actors. As evident in the making of the Islam clauses, these negotiations might be characterized as between puritan Islamist and more moderate Muslim actors.Keywords:Â constitution-making, Afghanistan, the 2004 Constitution, Islam clauses, Islamic.